2015
DOI: 10.1002/2015tc003845
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical and geochemical nature of relaminated arc‐derived lower crust underneath oceanic domain in southern Mongolia

Abstract: The Central Asian Orogenic Belt (CAOB) in southern Mongolia consists of E-W trendingNeoproterozoic cratons and Silurian-Devonian oceanic tectonic zones. Previous study revealed that the Early Paleozoic accretionary wedge and the oceanic tectonic zone are underlain by a layer giving a homogeneous gravity signal. Forward gravity modelling suggests that this layer is not formed of high-density material typical of lower oceanic crust but is composed of low-to intermediate-density rocks resembling continental crust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 115 publications
(225 reference statements)
2
51
0
Order By: Relevance
“…The analysis of magnetic lineaments in SW Mongolia also demonstrates that the zones of magnetic highs coincide with other E-W trending Late Paleozoic volcano-plutonic provinces previously defined by Kovalenko et al (2006) as continental rifts related to Pacific-type geodynamic processes and protracted activity of mantle plumes (Yarmolyuk et al 2014). Indeed the geophysical lineaments and magmatic zones can be interpreted as tectono-magmatic deformation zones deeply rooted in the lithosphere that probably channelled mantle-derived magmas (Guy et al 2015). Our data confirm the idea that Late Carboniferous was a period of elevated thermal structure at the lithospheric scale, but the crust was molten heterogeneously leading to localized emplacement of magmas along E-W oriented lineaments.…”
Section: Geodynamic Contextmentioning
confidence: 97%
See 2 more Smart Citations
“…The analysis of magnetic lineaments in SW Mongolia also demonstrates that the zones of magnetic highs coincide with other E-W trending Late Paleozoic volcano-plutonic provinces previously defined by Kovalenko et al (2006) as continental rifts related to Pacific-type geodynamic processes and protracted activity of mantle plumes (Yarmolyuk et al 2014). Indeed the geophysical lineaments and magmatic zones can be interpreted as tectono-magmatic deformation zones deeply rooted in the lithosphere that probably channelled mantle-derived magmas (Guy et al 2015). Our data confirm the idea that Late Carboniferous was a period of elevated thermal structure at the lithospheric scale, but the crust was molten heterogeneously leading to localized emplacement of magmas along E-W oriented lineaments.…”
Section: Geodynamic Contextmentioning
confidence: 97%
“…Geophysical study of Guy et al (2014b) has shown that this tectono-magmatic zone spatially coincides with a strong, c. 15-20 km deep magnetic lineament. The analysis of magnetic lineaments in SW Mongolia also demonstrates that the zones of magnetic highs coincide with other E-W trending Late Paleozoic volcano-plutonic provinces previously defined by Kovalenko et al (2006) as continental rifts related to Pacific-type geodynamic processes and protracted activity of mantle plumes (Yarmolyuk et al 2014).…”
Section: Geodynamic Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Terrane maps of Mongolia with accompanying stratigraphic columns and geochronological data provide a regional lithotectonic framework for understanding the region's crustal evolution [4,21]. More recently, new maps, structural and geochronological data, and gravity and magnetic models from different areas in southern Mongolia further refine the polyphase metamorphic, deformational, and magmatic evolution of the different terranes and call into question the locations of some previously mapped terrane boundaries [8,20,22].…”
Section: Paleozoic Terrane Assembly Of the Southern Caob In The Gobi mentioning
confidence: 99%
“…The continental crust of southern Mongolia and the Beishan region consists of a Paleoproterozoic basement complex in southern Mongolia surrounded by various lower through upper Paleozoic arc, accretionary prism/melange, and ophiolitic complexes [4,9,19,20]. Terrane maps of Mongolia with accompanying stratigraphic columns and geochronological data provide a regional lithotectonic framework for understanding the region's crustal evolution [4,21].…”
Section: Paleozoic Terrane Assembly Of the Southern Caob In The Gobi mentioning
confidence: 99%